2012
DOI: 10.3391/mbi.2012.3.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Management of invasive plant species in Nigeria through economic exploitation: lessons from other countries

Abstract: Invasive alien species, once they made entry into a region or country, often become difficult to eradicate and it appears that they have cometo stay. Worse still, their adverse effects on the native biodiversity are enormous and they are considered ecologically harmful. Agriculturaland economic losses to invasive species are comparatively high. Mechanical control is expensive and difficult in some terrains; chemicalcontrol is also expensive, requires constant application and has its environmental implications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Research findings from the current investigation corroborate previous studies which showed that invasive alien plant species may also have positive socio-economic benefits (Zimmermann and Neser 1999;Njoroge et al 2004;Bigirimana et al 2011Bigirimana et al , 2012Semenya et al 2012a,b;Maroyi 2017aMaroyi ,b, 2018Semenya and Maroyi 2018). Borokini and Babalola (2012) argued that economic exploitation of invasive alien species is usually labor intensive and menial jobs are usually created while providing additional means of income for local communities. Similarly, Sladonja et al (2018) argued that invasive alien plants can be used as catalysts for ecosystem restoration, source of bioenergy, honey, fiber, ornamental plants, and herbal medicines.…”
Section: Perceptions and Utilization Of O Ficus-indicasupporting
confidence: 89%
See 1 more Smart Citation
“…Research findings from the current investigation corroborate previous studies which showed that invasive alien plant species may also have positive socio-economic benefits (Zimmermann and Neser 1999;Njoroge et al 2004;Bigirimana et al 2011Bigirimana et al , 2012Semenya et al 2012a,b;Maroyi 2017aMaroyi ,b, 2018Semenya and Maroyi 2018). Borokini and Babalola (2012) argued that economic exploitation of invasive alien species is usually labor intensive and menial jobs are usually created while providing additional means of income for local communities. Similarly, Sladonja et al (2018) argued that invasive alien plants can be used as catalysts for ecosystem restoration, source of bioenergy, honey, fiber, ornamental plants, and herbal medicines.…”
Section: Perceptions and Utilization Of O Ficus-indicasupporting
confidence: 89%
“…Similarly, Sladonja et al (2018) argued that invasive alien plants can be used as catalysts for ecosystem restoration, source of bioenergy, honey, fiber, ornamental plants, and herbal medicines. Exotic plant species are now regarded as an important component of traditional pharmacopeia in many developing countries (Bennett and Prance 2000;Alencar et al 2010Alencar et al , 2014Borokini and Babalola 2012;Maroyi 2018;Semenya and Maroyi 2018;Sladonja et al 2018).…”
Section: Perceptions and Utilization Of O Ficus-indicamentioning
confidence: 99%
“…Water hyacinth is a suitable media for mosquito reproduction [74,83] and for snails, which serve as vector for the parasite of Schistosomiasis [84]. It also provides cover to reptiles such as poisonous snakes [70].…”
Section: Impactsmentioning
confidence: 99%
“…However, the use of herbicides to control water hyacinth is only effective in the short term anywhere in the world (Borokoni and Babalola, 2012;Dagno et al, 2011). Biological control of water hyacinth, which involves the use of natural enemies (i.e.…”
Section: Introductionmentioning
confidence: 99%